2008
DOI: 10.1016/j.stem.2008.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Notch Signaling Is Dispensable for the Maintenance of Adult Hematopoietic Stem Cells

Abstract: Gain-of-function experiments have demonstrated the potential of Notch signals to expand primitive hematopoietic progenitors, but whether Notch physiologically regulates hematopoietic stem cell (HSC) homeostasis in vivo is unclear. To answer this question, we evaluated the effect of global deficiencies of canonical Notch signaling in rigorous HSC assays. Hematopoietic progenitors expressing dominant-negative Mastermind-like1 (DNMAML), a potent inhibitor of Notch-mediated transcriptional activation, achieved sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
251
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(276 citation statements)
references
References 69 publications
21
251
3
1
Order By: Relevance
“…The same holds true for conditional RBP-J deficient mice [68]. In addition, in mice reconstituted with stem cells carrying a dominant negative form of Mastermind (dnMAML, see above), development of myeloid compartment is also not affected [136]. For further detailed information, readers are referred to several excellent in-depth reviews on the topic of Notch signaling in hematopoiesis, especially lymphopoiesis [107,140,153,154].…”
Section: Notch and B-cell Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…The same holds true for conditional RBP-J deficient mice [68]. In addition, in mice reconstituted with stem cells carrying a dominant negative form of Mastermind (dnMAML, see above), development of myeloid compartment is also not affected [136]. For further detailed information, readers are referred to several excellent in-depth reviews on the topic of Notch signaling in hematopoiesis, especially lymphopoiesis [107,140,153,154].…”
Section: Notch and B-cell Developmentmentioning
confidence: 97%
“…Neither inducible knock-out of RBP-J [68], Notch1 [134] or Jagged1 [135] have led to a reduction of hematopoietic stem cells. In addition, Pear and colleagues showed that HSCs that carry dominantnegative mastermind (dnMAML) can engraft normally in bone-marrow transplantation assays, and that normal frequencies in long-term reconstitution assays are achieved in both the presence or absence of dnMAML [136].…”
Section: Notch In Hematopoiesismentioning
confidence: 99%
“…At least three studies with loss-offunction mutants in critical components of the Wnt pathway provide evidence that canonical Wnt signaling plays a functional role in hematopoiesis and lymphopoiesis [2][3][4]. These are studies with Wnt3a-deficient mice, DKK1 transgenic mice and mice with a T-cell specific deletion of b-catenin.…”
Section: Responsementioning
confidence: 99%
“…Notch signaling plays an active role in tissue homeostasis, with initially studies first describing its role in embryonic development. 65,74,75 In humans, Delta-like and/or Jagged ligands bind to four Notch receptors, and studies suggest that Notch activation may to play some role in HSCs maintenance and/or expansion. 51,65 In fact, recent work has found that Notch activation can be utilized to expand primitive HSCs for transplantation.…”
Section: Regulation Of Expression Via Cell Membrane Proteinsmentioning
confidence: 99%
“…76 However, it remains unclear if Notch is required for perpetual maintenance of these cells. 65,74,75 WNT signaling may also play some role in promoting the expansion of primitive HSCs and has been implicated in HSCs selfrenewal. 75 Although Notch and WNT pathways represent the "state-of-the-art" in our understanding of how membrane receptors influence hematopoiesis, many aspects of these receptors' biology remains unknown, highlighting the need for additional studies.…”
Section: Regulation Of Expression Via Cell Membrane Proteinsmentioning
confidence: 99%